2021
DOI: 10.3390/jcm10051113
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Allogeneic Hematopoietic Stem Cell Transplantation on Kidney Function in Children—A Single Center Experience

Abstract: Background: Knowledge about the impact of allogeneic hematopoietic stem cell transplantation (alloHSCT) on renal function in children is still limited. Objectives: The aim of the study was to evaluate kidney function in children undergoing alloHSCT, with special focus on differences between patients transplanted due to oncological and non-oncological indications. Materials and Methods: The data of 135 children undergoing alloHSCT were analyzed retrospectively. The serum creatinine and estimated glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Representative studies that focus on the association of AKI with transplant outcomes are shown in Table 2. In pediatric HCT recipient, the incidence of AKI is similar to adults (44,48,49,(56)(57)(58), AKI worsens mortality after HCT (49,57), and the 1-year survival rate is less than 10% in patients with renal failure requiring renal replacement therapy (56). Fortunately, HCT-related AKI has decreased in recent years due to the increased use of less toxic conditioning regimens, decreased rates of SOS, modified infection prophylaxis, less amphotericin B use, and declining rates of severe aGVHD (59,60).…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative studies that focus on the association of AKI with transplant outcomes are shown in Table 2. In pediatric HCT recipient, the incidence of AKI is similar to adults (44,48,49,(56)(57)(58), AKI worsens mortality after HCT (49,57), and the 1-year survival rate is less than 10% in patients with renal failure requiring renal replacement therapy (56). Fortunately, HCT-related AKI has decreased in recent years due to the increased use of less toxic conditioning regimens, decreased rates of SOS, modified infection prophylaxis, less amphotericin B use, and declining rates of severe aGVHD (59,60).…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
“…Whether the indication for HCT is for a malignant or nonmalignant disorders does not significantly affect the incidence of AKI ( 33 , 48 , 49 ). However, malignancies are a risk factor for post-transplant CKD ( 50 ), and these patients should be monitored carefully for changes in renal function.…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
“…One of the examples is the recently published data on renal function and AKI incidence in children undergoing hematopoietic stem cell transplantation (HSCT), who are classified by RAI as those at high risk of developing AKI. Most of the pediatric patients presented with hyperfiltration even before the procedure and its presence was correlated with previous chemotherapy [ 40 ]. Of note, the percentage of children with increased eGFR values was the highest among those who have undergone HSCT for oncological reasons.…”
Section: How To Prevent Kidney Injury In Children?mentioning
confidence: 99%
“…A recent and interesting retrospective study by Musiał et al [ 101 , 102 ] evaluated renal function in children undergoing allogenic-HSCT, analyzing the possible differences between patients transplanted for oncological causes compared to those transplanted for non-oncological causes. The authors concluded that children undergoing HSCT, both for oncological indications and for those non-oncological, have the same risk of developing AKI, as defined by Kidney Disease: Improving Global Outcome (KDIGO) [ 103 ] and pRIFLE criteria [ 104 ].…”
Section: Kidney Dysfunction After Hematopoietic Stem Cell Transplanta...mentioning
confidence: 99%